18-α-glycyrrhetinic acid alleviates oxidative damage in periodontal tissue by modulating the interaction of Cx43 and JNK/NF-κB pathways - Cao, Niuben; Liu, Xiaomeng; Hou, Yubo; Deng, Yu; Xin, Yu; Xin, Xirui; Xiang, Xinchen; Liu, Xinchan; Yu, Weixian (Frontiers in Pharmacology, 2023)
Periodontitis is a common chronic inflammatory disease in which oxidative stress is one of the key pathogenic factors. Connexin43 (Cx43) is the most critical and widely distributed connexin isoform. When the organism undergoes a severe and sustained stress response, Cx43-mediated gap junctions (GJs) are believed to underlie the biology of tissue injury exacerbation and amplification. Notably, 18α-glycyrrhetinic acid (GA) is a classical pharmacological inhibitor of GJs and has antioxidant potential. However, the regulatory role of GA in the redox signaling of periodontal tissues and the potential mechanisms of Cx43 in the pathogenesis of periodontitis remain uncertain. In this study, we evaluated the effects and mechanisms of GA in alleviating oxidative damage of periodontal tissues and cells by constructing an H2O2-induced oxidative stress model in human periodontal ligament cells (hPDLCs) and a periodontitis model in rats. The results showed that GA effectively attenuated H2O2-induced oxidative damage in hPDLCs by inhibiting the expression and function of Cx43. In addition, pretreatment of hPDLCs with either GA or SP600125 (a JNK inhibitor) inhibited the Cx43/JNK/NF-κB pathway, restored cell viability, and reduced apoptosis. Animal experiment results showed that GA intervention reduced alveolar bone resorption and periodontal tissue destruction, inhibited osteoclast differentiation, improved mitochondrial structural abnormalities and dysfunction in periodontal tissue, and decreased oxidative stress levels and apoptosis in rats with periodontitis. Overall, our findings suggest that the Cx43/JNK/NF-κB pathway may play a vital role to promote periodontitis progression, while GA reduces oxidative stress and apoptosis by inhibiting the interaction of Cx43 and JNK/NF-κB pathways, thus alleviating oxidative damage in the periodontal tissues.